Penguatan Literasi Ekologi Sosial Pesisir dan Valuasi Karbon Mangrove dalam Mendukung Eco Forest City di Medan Belawan - Suranto Suranto; Rahmawaty Rahmawaty; Isnen Fitri; Luthfi Hakim; Ismayadi Ismayadi; Darnianti Darnianti; Eling Tuhono; Suarno Suarno (PATRIOTIKA: Jurnal Inovasi dan Pemberdayaan Masyarakat, 2026)
Medan Belawan District is a strategic coastal area in Medan City that has important ecological, social, and economic functions. The presence of mangroves and urban trees in this area acts as green infrastructure that supports coastal protection, carbon storage, biota habitat, and urban environmental resilience. This community service activity aims to strengthen coastal social ecological literacy, increase participants' understanding of the carbon valuation of mangroves and urban trees, and encourage collective awareness in supporting the development of Eco Forest City in Medan Belawan. The activities were carried out through excursion studies, field observations, academic discussions, ecological data interpretation, and dissemination of results through online mass media. The community service material was supported by data on vegetation inventory, mangrove cover, tree health, carbon storage, carbon economic value, and priority management zoning. The results of the activity showed that mangroves are a dominant component of Medan Belawan's public green spaces, namely 157 of 218 inventory units or 72.02%. The dominant species is Avicennia marina with 105 individuals or 48.17%. Mangrove cover increased from 393.28 ha in 2005 to 1,110.00 ha in 2025. Carbon storage is estimated to reach 35,106 kg C or 128,840 kg CO2e, with a carbon economic value of Rp471,091,349. The outputs of the activity include increased participant literacy, recommendations for coastal green space management, activity documentation, community service articles, and news releases in Borneonews. This activity demonstrates that community service based on scientific data can be a bridge between research, field learning, communities, and coastal management policies.